1984
DOI: 10.1111/j.1365-2273.1984.tb01509.x
|View full text |Cite
|
Sign up to set email alerts
|

The anatomy of the lymph nodes of the parotid gland

Abstract: A series of 17 parotid glands were obtained by radical parotidectomy. Between 1 and 11 lymph nodes were found in them. Superficial parotidectomy only leaves an average of 1 node in the deep parotid. There is a 1 in 4 chance of there being no nodes left. There were no nodes easily accessible immediately under the deep part of the parotid gland. There seems to be a discrepancy between the number of nodes found in a radical surgical specimen and serial sections of the area. This suggests a significant number may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
26
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Although there were many discourses about the parotid lymph nodes, there were no anotomic and surgical studies with definite evidence until that time. 28,29 The first studies investigating the number of intraglandular lymph nodes in the literature were made by Marks 31 and McKean et al 29 In McKean et al's 29 study of 10 cadavers, IGLN was found in 100% of the superficial lobes, and the total number of lymph nodes was determined in the range of 2 to 22. In the study, the mean ILGN in the superficial lobe was 8.85, while it was 0.8 in the deep lobe and 91.7% of the total parotid nodes were found in the superficial lobe of the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there were many discourses about the parotid lymph nodes, there were no anotomic and surgical studies with definite evidence until that time. 28,29 The first studies investigating the number of intraglandular lymph nodes in the literature were made by Marks 31 and McKean et al 29 In McKean et al's 29 study of 10 cadavers, IGLN was found in 100% of the superficial lobes, and the total number of lymph nodes was determined in the range of 2 to 22. In the study, the mean ILGN in the superficial lobe was 8.85, while it was 0.8 in the deep lobe and 91.7% of the total parotid nodes were found in the superficial lobe of the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…However, Garatea-Crelgo et al and Pisani et al emphasize that because of the large number of lymph nodes in the deep lobe, superficial parotidectomy would be insufficient when radical neck dissection involving the parotid gland should be performed. 27,[29][30][31] When we look at the clinical studies, Jackson and Ballantyne, Santini et al, Caldwell and Spiro, and Ball and Thomas, in their studies evaluating head and neck metastases, reported that superficial parotidectomy provides local control in cases without significant involvement of the deep lobe. [32][33][34][35] However, Conley and Arena and Jackson and Ballantyne reported that 25% to 38% of cases required total parotidectomy later.…”
Section: Discussionmentioning
confidence: 99%
“…Such therapeutic attitude is not fully supported by the anatomical studies available, which consistently show that the vast majority of IGLNs are located superficially to the facial nerve. 14,26,27 Furthermore, the presence of IGLN metastases is significantly more prevalent in patients with advanced T status, and T status is in turn a major decisive factor when deciding the extent of surgery for the primary tumor. Consequently, there is a reasonable possibility that the higher prevalence of IGLN metastases found in total parotidectomy specimens is due to the stage of the primary tumor (which led to performing a total parotidectomy in the first place) rather than to the type of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…From cadaveric studies, we know that the majority of lymph nodes in the parotid gland are located in the superficial lobe. 5,6 Very few nodes are located in the deep lobe near the retromandibular vein and facial nerve. However, considering that the mean size of parotid metastases was 4.5 cm and that 39% of positive cervical nodes had extracapsular extension, deep lobe and facial nerve involvement is not surprising.…”
Section: Discussionmentioning
confidence: 99%